Detection of Stone Material Deterioration in Historical Masonry Buildings by Observational Methods: Mardin Former American Missionary College - Karataş, Lale (My University, 2023)
It is essential requirement to define the deterioration models correctly to understand the problems, and to determine the conservation needs and conservation acts, when investigating the stone buildings. Various deterioration types standardized as in the dictionary of ICOMOS are appropriate to achieve the stated objectives; however, these methodologies remain incapable to interpret the situation in complex cases. Therefore, deterioration types must be defined and mapped in accordance with their geographical contexts. Within the context of ensuring the continuity of these objectives in various countries, it is important to exemplify the determination and articulation stages intended for the material problems and interventions on the historical buildings systematically within the geographic context. The study conducted within this context is to exemplify the determination and articulation stages intended for the material problems and interventions systematically within the geographic context, based on Former American Missionary College Hospital case, to manage the material problems on historical masonry buildings in Mardin, which is a unique geographic context, in a sustainable manner. Mardin Former American Missionary College Hospital, which remains within the preserved urban archaeological site in Mardin, is a unique cultural monument, which survives over the years, despite exposure to many environmental influences. A classification was made to determine and document the material deteriorations regarding the Former American Missionary College Hospital. Literature research, determination via observation, and documentation through photographing methods were used in the study. The information obtained was assessed via the descriptive and systematic analysis methods. The study is expected to make contribution into the literature both in terms of addressing the stone material problems of Mardin Former American Missionary College Hospital and of exemplifying the deterioration types and conservation suggestions regarding the other buildings within this geographical context.
Keywords: Mardin; Conservation; Traditional Stone Building; Stone Deteriorations; Deterioration Types